2009
DOI: 10.1186/1471-230x-9-95
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community analysis reveals high level phylogenetic alterations in the overall gastrointestinal microbiota of diarrhoea-predominant irritable bowel syndrome sufferers

Abstract: Background: A growing amount of scientific evidence suggests that microbes are involved in the aetiology of irritable bowel syndrome (IBS), and the gastrointestinal (GI) microbiota of individuals suffering from diarrhoea-predominant IBS (IBS-D) is distinguishable from other IBS-subtypes. In our study, the GI microbiota of IBS-D patients was evaluated and compared with healthy controls (HC) by using a high-resolution sequencing method. The method allowed microbial community analysis on all levels of microbial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
170
6
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 260 publications
(205 citation statements)
references
References 58 publications
(96 reference statements)
14
170
6
6
Order By: Relevance
“…Decreased counts of bifidobacteria have been reported in IBS patients (Kerckhoffs et al, 2009;Malinen et al, 2005), especially of the B. catenulatum group (Kerckhoffs et al, 2009;Lyra et al, 2009;Malinen et al, 2005). A decrease of lactobacilli has been detected in IBS-D (Malinen et al, 2005;Krogius-Kurikka et al, 2009) and IBS-A patients (Kerckhoffs et al, 2009). On the other hand, untypically high faecal amounts of lactobacilli and/or streptococci have been reported for IBS-D patients (Kassinen et al, 2007;Krogius-Kurikka et al, 2009;Carroll et al, 2008) as well as IBS patients independent of the subtype (Tana et al, 2010).…”
Section: Microbiota In Different Ibs Subtypesmentioning
confidence: 97%
See 2 more Smart Citations
“…Decreased counts of bifidobacteria have been reported in IBS patients (Kerckhoffs et al, 2009;Malinen et al, 2005), especially of the B. catenulatum group (Kerckhoffs et al, 2009;Lyra et al, 2009;Malinen et al, 2005). A decrease of lactobacilli has been detected in IBS-D (Malinen et al, 2005;Krogius-Kurikka et al, 2009) and IBS-A patients (Kerckhoffs et al, 2009). On the other hand, untypically high faecal amounts of lactobacilli and/or streptococci have been reported for IBS-D patients (Kassinen et al, 2007;Krogius-Kurikka et al, 2009;Carroll et al, 2008) as well as IBS patients independent of the subtype (Tana et al, 2010).…”
Section: Microbiota In Different Ibs Subtypesmentioning
confidence: 97%
“…A decrease of lactobacilli has been detected in IBS-D (Malinen et al, 2005;Krogius-Kurikka et al, 2009) and IBS-A patients (Kerckhoffs et al, 2009). On the other hand, untypically high faecal amounts of lactobacilli and/or streptococci have been reported for IBS-D patients (Kassinen et al, 2007;Krogius-Kurikka et al, 2009;Carroll et al, 2008) as well as IBS patients independent of the subtype (Tana et al, 2010). This trend suggests that at least some IBS patients, similarly to ileostomy patients, have an outgrowth of aerobic bacteria that may be linked to the overproduction of organic acids, as will be discussed below.…”
Section: Microbiota In Different Ibs Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Recent studies of the microbiota in adults with different IBS subtypes have also confirmed specific gut bacterial dysbiosis, with a decrease in bifidobacteria in IBS-D patients and increase in Gammaproteobacteria. [61][62][63] Furthermore, several species have now been correlated with a lower or higher severity as well as frequency of pain in children (Fig. 3) and warrant further investigation.…”
Section: The Association Between Intestinal Microbiome and The Brain-mentioning
confidence: 99%
“…The most distinctive symptom sub-type is IBS-D, which could also be a result of the impact of the diarrhoea on the microbial environment in the gut. In addition, comparatively low quantities of bifidobacteria, which are generally considered beneficial to health, have been detected in several IBS studies (Balsari et al, 1982;Enck et al, 2009;Kerckhoffs et al, 2009;Krogius-Kurikka et al, 2009;Si et al, 2004). This finding, though still preliminary, encourages development of probiotic and prebiotic therapies for IBS.…”
Section: Introductionmentioning
confidence: 90%